Comparison of non-coding RNAs in human and canine cancer - Wagner, Siegfried; Willenbrock, Saskia; Nolte, Ingo; Murua Escobar, Hugo (Frontiers in Genetics, 2013)
The discovery of the post-transcriptional gene silencing by small non-protein-coding RNAs is considered as a major breakthrough in biology. In the last decade we just started to realize the biologic function and complexity of gene regulation by small non-coding RNAs. Post-transcriptional gene silencing (PTGS) is a conserved phenomenon which was observed in various species such as fungi, worms, plants and mammals. Micro RNAs (miRNA) and small interfering RNAs (siRNAs) are two gene silencing mediators constituting an evolutionary conserved class of non-coding RNAs regulating many biological processes in eukaryotes. As this small RNAs appear to regulate gene expression at translational and transcriptional level it is not surprising that during the last decade many human diseases among them Alzheimer's disease, cardiovascular diseases and various cancer types were associated with deregulated miRNA expression. Consequently small RNAs are considered to hold big promises as therapeutic agents. However despite of the enormous therapeutic potential many questions remain unanswered. A major critical point, when evaluating novel therapeutic approaches, is the transfer of in vitro settings to an in vivo model. Classical animal models rely on the laboratory kept animals under artificial conditions and often missing an intact immune system. Model organisms with spontaneously occurring tumors as e.g. dogs provide the possibility to evaluate therapeutic agents under the surveillance of an in intact immune system and thereby providing an authentic tumor reacting scenario. Considering the genomic similarity between canines and humans and the advantages of the dog as cancer model system for human neoplasias the analyses of the complex role of small RNAs in canine tumor development could be of major value for both species. Herein we discuss comparatively the role of miRNAs in human and canine cancer development and highlight the potential and advantages of the model organism dog for